O itinerário de Ody Fraga rumo ao cinema - Mamigonian, José Rafael Gallotti (2022)
This research aims to investigate the initiation path of screenwriter and film director Ody Fraga (1927–1987). We chose to approach the period that precedes the making of his first feature film "Vidas Nuas" (1967), originated from an unfinished project entitled "Erótica". To retrace his long journey, we go back to his childhood, adolescence, as well as his early work in journalism and theater. We work with different documentary sources, seeking to establish little-known information about the director's life trajectory and “immature work”, reflecting on aspects of his intellectual production throughout this period.